1985
DOI: 10.1007/bf01309821
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of infection and selective loss of Ia positive cells in suckling and adult mice inoculated with lactic dehydrogenase virus

Abstract: Lactic dehydrogenase virus (LDV) infected cells were localised in cryostat sections of infected adult and suckling mice by fluorescent antibody staining. In almost every organ except brain and spinal cord, LDV infected cells were present in interstitial connective tissue, including dermis and submucosa of gastrointestinal and urinogenital tracts. They were also present in liver sinusoids and red pulp of spleen. The tissue distribution, shape, and fluorescence staining pattern of infected cells were similar in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…(Porter & Porter, 1971 ;Inada & Mims, 1985;Chan et al, 1989), these findings being consistent with the cytocidal nature of LDV replication in macrophages (Plagemann & Moennig, 1992). Similarly, LDV-infected cells have been detected in sections of the spleen by in situ hybridization and by electron microscopy at 1 day p.i., but not at later times (Stueckemann et al, 1982a;Chan et al, 1989) and the same applies to the detection of LDV genomic and subgenomic mRNAs in the spleens by using Northern hybridization analysis (Contag & Plagemann, 1989;Kuo et al, 1992).…”
Section: R R Rowland and Otherssupporting
confidence: 54%
See 1 more Smart Citation
“…(Porter & Porter, 1971 ;Inada & Mims, 1985;Chan et al, 1989), these findings being consistent with the cytocidal nature of LDV replication in macrophages (Plagemann & Moennig, 1992). Similarly, LDV-infected cells have been detected in sections of the spleen by in situ hybridization and by electron microscopy at 1 day p.i., but not at later times (Stueckemann et al, 1982a;Chan et al, 1989) and the same applies to the detection of LDV genomic and subgenomic mRNAs in the spleens by using Northern hybridization analysis (Contag & Plagemann, 1989;Kuo et al, 1992).…”
Section: R R Rowland and Otherssupporting
confidence: 54%
“…Faaberg, C. Even & P. G. W. Plagemann, unpublished). In adult mice, 5 weeks or older, 5 to 10% of peritoneal macrophages are permissive for LDV replication, whereas in mice younger than 2 weeks of age the proportion of permissive peritoneal macrophages is 60 to 80 % (Inada & Mims, 1985;Onyekaba et al, 1989b). Infection of these macrophages both in vitro and in vivo is cytocidal (Onyekaba et al, 1989b).…”
Section: Introductionmentioning
confidence: 99%
“…1B, there is no difference between IL-6 activities with and without indomethacin. Most functional alterations of macrophages may be due to cyclooxygenase products after interaction between IC and Fc receptor on macrophages other than direct viral infection in chronically LDV-infected mice [4,7] , since macrophages infected with LDV were less than 10% [10]. Unexpectedly, IL-6 production by macrophages is not impaired in the chronic infection of mice, suggesting that the depressed humoral response to T cell dependent antigens seen in chronic phase of infection [17] may not be involved in the depressed IL-6 production by macrophages as reported here.…”
mentioning
confidence: 99%
“…Moreover, the present results suggest that cyclooxygenase products, especially PGEs, one of the regulators of macrophage function such as Ia antigen expression [5,18], IL-1 production [4], and spreading, adhesion and migration [2], may not affect IL-6 production. In addition, though LDV infection causes suppression of autoimmune diseases [3,5,6,10,16], these phenomena may not be due to, at least in part, impaired macrophage IL-6 production, which is known as an enhancer of autoimmune diseases [1,9] . We could not eliminate the possibility that IL-6 production from other immunocompetent cells especially helper T2 cells [13] might be suppressed, since it has been suggested that defective helper T cell function was reported in chronically LDV-infected mice [11].…”
mentioning
confidence: 99%
“…LDV was donated by Dr K. E. K. Rowson and stock virus preparations were made by collecting serum from mice infected 24 h previously. The assay method has been described (Inada & Mims, 1985 a). The strain and stock virus preparation of murine cytomegalovirus (MCMV) used have also been described (Chong & Mims, 1982).…”
Section: Methodsmentioning
confidence: 99%